IMPROVING STUDENTS’ READING COMPREHENSION OF VII GRADE AT MTs. Hi. HAYYUN SALUMPAGA BY USING HUMOR STORIES - Reza Aprilieah (Jurnal Madako Education, 2017)
The objective of this research is to improve students reading comprehension of the VII grade of MTs. Hi. Hayyun Salumpaga by using humor story. This research belongs to experimental design following the three step is pretest, treatment, posttest. The population of the research is the VII grade students of MTs. Hi. Hayyun Salumpaga. The data were analyzed by using experimental analysis in order to know the significant difference of the achievement of the students in pretest and posttest. By applying 0.05 level of significant, the researcher find out that tcount 5.900 is higher than ttable 2.060. It is suggested that humor story in teaching English can be recommended for the English teacher. But the English teacher a hold select appropriate humor story to the students.Key Word: Improving, Reading Comprehension, Humor Story.